Twenty-four years of prescription patterns in bipolar disorder inpatients with vs without lithium: a pharmacoepidemiological analysis of 8,707 cases in German-speaking countries - Waldemar Greil; Mateo de Bardeci; Nadja Nievergelt; Andreas Erfurth; Gregor Hasler; Rene Bridler; Sermin Toto; Renate Grohmann; Johanna Seifert; Georgios Schoretsanitis (International Journal of Bipolar Disorders)
Abstract Background Global pharmacoepidemiological evidence suggests dynamically changing prescription patterns in patients with bipolar disorders. We assessed trends in the use of pharmacological agents used in the management of bipolar disorders in inpatients. Methods We examined drug use data provided by the Drug Safety in Psychiatry Programme AMSP (German: “Arzneimittelsicherheit in der Psychiatrie”), including psychiatric hospitals in Germany, Austria and Switzerland. We included data from adult inpatients with bipolar disorders (ICD-10: F31) treated between 1994 and 2017. We compared prescription patterns between patients receiving therapeutic regimens with vs. without lithium. Patients with manic and depressive episodes were also analyzed separately. Results We identified a total of 8,707 patients (58% females, mean age 50.8 ± 14.8 years). Our analysis revealed a decrease of lithium use (up to 2004) and a consistent increase of prescription rates for second-generation antipsychotics (SGA) among which quetiapine (n = 2,677) and olanzapine (n = 1,536) were the most common. Among psychotropic drugs, quetiapine was most frequently combined with lithium (n = 716, 25.6%). Lithium-treated patients received a higher number of drugs compared to patients not receiving lithium (mean number of drugs in patients with vs. without lithium 4.99, n = 2,796 vs. 4.75, n = 5,911, p = 0.002). Thyroid therapeutics were given more often, valproate and quetiapine less often in the lithium group. Antidepressants were consistently prescribed to more than 60% of patients with bipolar depressive episodes. Conclusions Our findings suggest that SGAs are gradually becoming the mainstay treatment option in bipolar disorder, continuously replacing lithium. The use of antidepressants remains concerningly high. We call for action to improve adherence to evidence-based guidelines.